PENGARUH MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DI KANTOR CAMAT MAZO KABUPATEN NIAS SELATAN - Natalius Hulu (Jurnal Ilmiah Mahasiswa Nias Selatan, 2022)
The purpose of this study was to determine the effect of work motivation on employee performance at the Mazo Sub-district Office, South Nias Regency. This type of research is quantitative research. The population in this study was all employees at the Mazo Sub-district Office, South Nias Regency. The number of samples in this study was 30 respondents. The data collection technique used is a questionnaire using a measurement scale, namely a likert scale. The research instrument test consists of a validity test and a reliability test; The classical assumption test consists of a normality test and a heteroskedasticity test. The data analysis technique in this study is a simple linear regression analysis. The results of this study show that partially the work motivation variable (X) affects employee performance (Y). simultaneously showed that the work motivation variable (X) had a positive and significant effect on the variable (Y) with acalculated t value of 4.736 > ttable l 1.701 with a significant level of 0.000 < 0.05. The value of the coefficient of determination (R2) is 0.445 so that it can be interpreted that the performance of employees at the Mazo Sub-district Office of South Nias Regency can be explained by the work motivation variable of 44.5% while the remaining 55.5% is explained by other variables outside the model.